2019
DOI: 10.1186/s12944-019-0997-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and arterial stiffness in Japanese population: a secondary analysis based on a cross-sectional study

Abstract: Background Evidence regarding the relationship between estimated glomerular filtration rate (eGFR) and arterial stiffness is limited, and the data analysis is not sufficient to clarify the true relationship between the two. We aimed to investigate the relationship between eGFR and brachial-ankle pulse wave velocity (baPWV) in Japanese. Methods The present study was a cross-sectional study. Nine hundred twelve Japanese men and women, aging 24—84 years old, received a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In our study, all renal function formulas showed a significant correlation. It should be noted that some studies have not found a link between mild renal impairment and arterial stiffness [ 10 , 11 ]. These two studies, respectively, adopted the Japanese Society of Nephrology model and MDRD formula to calculate eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all renal function formulas showed a significant correlation. It should be noted that some studies have not found a link between mild renal impairment and arterial stiffness [ 10 , 11 ]. These two studies, respectively, adopted the Japanese Society of Nephrology model and MDRD formula to calculate eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…There are many formulas for calculating renal function in CKD patients, and the correlation between different formulas and arterial stiffness is still controversial. A study has suggested that the relationship between estimated glomerular filtration rate (eGFR) and arterial stiffness is nonlinear [ 10 ]. Moderate to severe renal impairment is associated with increased arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were stratified by eGFR quartile into Q1 (<82.88 ml/min/1.73 m 2 ), Q2 (≥82.88, <99.70), Q3 (≥99.70, <116.56), and Q4 (≥116.56) groups (43)(44)(45). For continuous variables, the mean (standard deviation) or median (range) (non-normal distribution) was used, and for categorical variables, the number (%) was used.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduced lateral collinearity we must avoid the reuse of predictors that were already used to estimate the outcome. Then this type of bias occurs when the outcome is derived from the predictors [4][5][6] as in body mass index (BMI), which is calculated as a function of height, and weight, and the KDPI, which is calculated using 6 donors variables. As an example of lateral collinearity in the study by Das et al [10], glomerular filtration was estimated with laboratory data and conclusions are drawn from regression based on age, ethnicity, and sex, variables that are also used to estimate GFR.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated glomerular filtration rate (eGFR), calculated using age, ethnicity, gender and creatinine values in the MDRD [1] and CKD-EPI [2] equations, has been used as an appropriate surrogate for glomerular function [3]. The eGFR has been used as an outcome in several epidemiological studies [4][5] including in transplantation [6] and is frequently considered as a surrogate marker in clinical studies.…”
Section: Introductionmentioning
confidence: 99%